Large size citrate‐reduced gold colloids appear as optimal SERS substrates for cationic peptides. (5th July 2016) - López‐Tobar, Eduardo; Hernández, Belén; Chenal, Alexandre; Coïc, Yves‐Marie; Gómez Santos, Johanna; Mejía‐Ospino, Enrique; Garcia‐Ramos, José Vicente; Ghomi, Mahmoud; Sanchez‐Cortes, Santiago
Abstract : Surface‐enhanced Raman spectra of two cyclic cationic peptides with therapeutic interest, somatostatin‐14 and its synthetic analog octreotide, were simultaneously analyzed as a function of concentration and colloidal size. It appeared that the large size ( 95 nm) citrate‐reduced gold nanoparticles are the most adequate substrates for providing an optimal Raman signal enhancement within the 10 −6 –10 −7 m peptide concentration range. It could also be evidenced that these large size particles can give rise to such a remarkable result within the first month following their elaboration. In fact, the recorded Raman spectra after this period mainly originate from the molecular species in the coverage of gold particles and not from the adsorbed peptides. To bring clarification to the temporal evolution of gold colloids, a systematic analysis was performed during 3 months on different particle sizes in the 15–150 nm range. The data obtained by a combined use of different techniques (Ultraviolet‐visible absorption, z‐potential, transmission electron microscopy, and Raman scattering) are consistent with a permanent evolution of the colloidal coverage, assignable to the gradual transformation of citrate anions and their substitution by oxidized products. It can be concluded that only small and medium size nanoparticles (≤ 40 nm) are able to regenerate their initial features after the first month, while large size colloids are subjected to a continuous degradation of their plasmonic and electrostatic properties. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Surface‐enhanced Raman spectra of two cyclic cationic peptides were simultaneously analyzed as a function of concentration and colloidal size. Large size ( 95 nm) citrate‐reduced gold nanoparticles are shown to be the most adequate substrates for providing an optimal Raman signal enhancement within the 10 −6 –10 −7 m peptide concentration range. Ultraviolet‐visible absorption, z‐potential, transmission electron microscopy, and Raman data are consistent with a permanent evolution of the colloidal coverage, assignable to the gradual transformation of citrate anions and their substitution by oxidized products.